Snowpiercer. The complete second season [videorecording (DVD)] - Friedman, Josh; Manson, Graeme (Writer) (Warner Bros. Home Entertainment, 2021)
As Season One ended, so did the revolution, with Layton emerging as Snowpiercer's leader and another threat to the survivors fast approaching in the form of a rival train. In Season Two, Mr. Wilford arrives, bringing a secret from Melanie's past. A new power struggle emerges, causing a dangerous rift as people are divided between their loyalties to Layton and to Mr. Wilford, who has a new train, new technology and a game plan that keeps everyone guessing. While Layton battles Wilford for the soul of Snowpiercer, Melanie leads the charge over a shocking new discovery that could change the fate of humanity.